Diagnostic Accuracy of Ultrasound in Detecting Ureteric Calculi as Compared to Computed Tomography taken as Gold Standard - Mian Ahmed Mustafa, Ahmad Ammar Arshad, Zahid Hafeez, Rana Shahid Hafeez, Arslan Saleem Chughtai, Sadaf Abdul Qadir, Mehwish Tahir, Muhammad Zakir (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the radiological findings for ureteric calculi on Computed Tomography and Ultrasound. Methodology: In this cross sectional survey medical records of 51 patients, underwent CT KUB and Ultrasound KUB at Shalimar Hospital, visited during January 1st, 2021 to June 30th, 2021 were considered in the study. A comparison was done between the radiological findings of the USG and CT reports. CT was kept as a gold standard, and the detection of hydro-nephrosis, hydro ureter on USG was checked. Also a comparison was done on the number, size and location of stones detected on both modalities. Results: Among the patients 34 were males and 17 were female. The mean age of male patients was 42 whereas mean age of female patients was 40. The specificity and sensitivity of ultrasound for detecting ureteric calculi was 44.12% and 100%, hydronephrosis was 90% and 88% whereas for hydro ureter was 72% and 100% respectively as compared to Computed tomography. Conclusion: It can be concluded from this study that there is an agreement between USG and CT finding for ureteric calculi. USG is cost effective than CT and equally effective in detecting hydronephrosis, hydro-ureter and ureteric calculi. Keywords: Ureteric Calculi, Hydronephrosis, Hydroureter, Flank Pain, Computed tomography, Ultrasound.